Application of horticulture therapy as a health intervention for elderly people in nursing homes: a scoping review† - Wang Jing-Jing; Niu Xiao-Yu; Zhao Ming-Li (Sciendo, 2024)
To review the scope of interventional studies on horticultural therapy (HT) applied to elderly people in nursing institutions to support the efficient implementation of HT among this target group.